Development of an animal model for type II sulcus (sulcus vergeture) - ENVER, NECATİ (My University, 2023)
Objectives: To develop a reproducible experimental animal model for sulcus vergeture in rabbits. Study Design: Experimental animal study. Material Method: We evaluated three methods of inducing sulcus in twelve New Zealand white rabbits to produce a sulcus model. Experimental groups comprised: group 1 (n = 4) underwent submucosal injury following endolaryngeal epithelial incision; group 2 (n = 4) received submucosal injury via thyrotomy; group 3 (n = 4) received submucosal injury via thyrotomy, followed with horizontal mucosal lateralization suture. Right vocal folds of the rabbits underwent surgery to produce sulcus vocalis and left vocal folds were used for the comparison. In the sixth week after the procedure, the rabbits were sacrificed and the larynxes were harvested and analyzed histopathologically. Results: No animals in group 1 or 2 developed sulcus vocalis. Sulcus formation was observed in all rabbits in group 3, under endoscopic examination and microscopic sulcus formation was demonstrated for the first, second, and third rabbits. An epithelial depression area was seen at the glandular ductal opening zone for the fourth rabbit, but it could also be accepted as a sulcus formation. Conclusion: We successfully developed a reproducible survival model for sulcus using a submucosal injury via thyrotomy, followed with a horizontal mucosal lateralization suture. This model provides the groundwork for future research into the applicability of new approaches for sulcus management.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kulak Burun Boğaz; Hemşirelik; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Otolaryngology; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; KULAK BURUN BOĞAZ; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; OTORHINOLARYNGOLOGY; Konuşma ve İşitme; LPN ve LVN; Otorhinolaryngology; Speech and Hearing; LPN and LVN; Experimental sulcus modeling—Larynx—Sulcus vocalis—Vocal fold; Experimental sulcus modeling; Larynx; Sulcus vocalis; Vocal fold